THE ROLE OF EMOTIONAL INTELLIGENCE ON ENGLISH SPEAKING SKILLS IN UNDERGRADUATE ENGLISH AS A FOREIGN LANGUAGE (EFL) STUDENTS - Nadira Ghiffari; Riki Ruswandi; Paulina Novarita (Universitas Muhammadiyah Metro, 2025)
Emotional intelligence (EI) is still rarely studied in the context of English-speaking skills, particularly in terms of its specific impact on speaking skills among undergraduate students. Therefore, this study aims to investigate the relationship between emotional intelligence (EI) and English-speaking skills among EFL students at Islamic Nusantara University in Bandung. A survey design involving 93 English Language Education students was employed, utilizing a quantitative approach selected through purposive sampling. This study employs a quantitative approach using a survey design. The data collection technique employed a questionnaire with a 5-point Likert scale, which was analyzed using descriptive statistics. The study results indicate that emotional intelligence (EI) has a significant impact on the English-speaking abilities of EFL students, playing a crucial role in enhancing confidence, managing anxiety, and improving speaking skills. An average score of 3.99 reflects students’ perception that EI plays a significant role in the success of speaking English. This study’s implications highlight the integration of EI lessons into the English learning curriculum to enhance students’ confidence and speaking skills, thereby creating a more satisfying learning experience. This research offers valuable insights for educators and curriculum developers to design programs that promote the development of emotional intelligence (EI) in the context of language learning, thereby enhancing students’ English-speaking skills.